A Cross-National Validation of the Shortened Version of the Adolescent Stress Questionnaire (ASQ-S) Among Adolescents From Switzerland, Germany, and Greece - Ertanir, Beyhan; Rietz, Christian; Graf, Ulrike; Kassis, Wassilis (Frontiers in Psychology, 2021)
The experience of stress is receiving increasing attention in the context of adolescent mental health, which is why a valid and reliable stress assessment instrument is of great importance. For this purpose, an English-language adolescent stress questionnaire (ASQ) was developed, which assesses the subjective stress experience of adolescents in different areas of life (e.g. at home, at school, and during leisure time). However, the latest long version of the questionnaire with 56 items (ASQ-2) was found to be too extensive, so a more economical short version ASQ-S with 27 items was developed. The aim of this study was to validate a German and a Greek version of the ASQ-S. In order to investigate the psychometric properties of the German and Greek ASQ-S confirmatory factor analysis, analyses of variance and correlations were applied to sample data from Switzerland, Germany and Greece (N = 1,071 seventh-grade students; Mage = 12.53; SD = 0.76). The results yielded only poor to moderate internal reliability across all three countries and the suggested 9-dimensional factor structure could not be confirmed. Instead, a modified 6-factor structure was tested which showed acceptable model fits while demonstrating form invariance across the three countries. Furthermore, the ASQ-S scales correlated positively with depressive symptoms and anxiety and negatively with self-esteem and life satisfaction, all of which supported adequate concurrent validity. The results revealed that the utility of the ASQ-S appears to be limited when translated to other languages and should be used with caution when administered in international contexts.